Neural Correlates of Long-Term Memory Enhancement Following Retrieval Practice - Marin-Garcia, Eugenia; Mattfeld, Aaron T.; Gabrieli, John D. E. (Frontiers in Human Neuroscience, 2021)
Retrieval practice, relative to further study, leads to long-term memory enhancement known as the “testing effect.” The neurobiological correlates of the testing effect at retrieval, when the learning benefits of testing are expressed, have not been fully characterized. Participants learned Swahili-English word-pairs and were assigned randomly to either the Study-Group or to the Test-Group. After a week delay, all participants completed a cued-recall test while undergoing functional magnetic resonance imaging (fMRI). The Test-Group had superior memory for the word-pairs compared to the Study-Group. While both groups exhibited largely overlapping activations for remembered word-pairs, following an interaction analysis the Test-Group exhibited differential performance related effects in left putamen and left inferior parietal cortex near the supramarginal gyrus. The same analysis showed the Study-Group exhibited greater activations in the dorsal MPFC/pre-SMA and bilateral frontal operculum for remembered versus forgotten word-pairs, whereas the Test-Group showed the opposite pattern of activation in the same regions. Thus, retrieval practice during training establishes a unique striatal-supramarginal network at retrieval that promotes enhanced memory performance. In contrast, study alone yields poorer memory but greater activations in frontal regions.